POLITIK PENYEDERHANAAN SISTEM KEPARTAIAN DI INDONESIA PASCA REFORMASI 1998 - Agus Sutisna (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
Since the 1999 elections electoral democracy Indonesia is marked by drastic changes in the party system implementation, from simple multi-party system in the New Order era to the extreme multiparty system. Judging from the election as the most massive space is provided to facilitate the political participation of the people, multiparty phenomenon is certainly a sign that democracy was growing. But in terms of the need to realize the importance of a stable and effective government, multiparty phenomenon is actually not a wise choice. Scott Mainwaring comparison study results conclude that the application of a multi-party system with a presidential system is a bad combination. That is why since the 2004 elections simplification efforts of party system in Indonesia is done through various policy strategy. This paper is a study about the application of extreme multiparty system and its impact on the election, the behavior of political parties in Parliament, and the relation of Parliament-President; and political strategy or policy simplification of party system that has been taken in Indonesia after the reform to realize a simple multiparty system. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i2.2816